SOCIAL PARTICIPATION OF OLDER PEOPLE AS EMPOWERMENT FACTOR - Tatyana S. Kienko (Векторы благополучия: экономика и социум, 2023)
The relevance of the article is caused by the challenges and changes in modern Russian society, in relation to which the role and demand for both social work in general and technologies for caring for a person are growing, which do not deprive him of subjectivity, but, on the contrary, allow him to overcome the role of an object of care, to go out on his own from difficult life situations, to take responsibility and control over life. One such tool of social support is empowerment. The purpose of the article is to identify the features of «empowerment» technique in social work and social practice and substantiate the role of social participation as its key factor on the example of social participation practices of older people. Research methods: systematic and comparative approach, thematic review and interpretive analysis of scientific literature, method of comparative analysis of the practices of social participation of older people. Results. The analysis allows us to highlight the key features of «empowerment» as a social technique for stimulating activity and social subjectivity in older age: a resource approach and reliance on human strengths, involvement in social participation practices, giving people real powers, equality and partnership. We believe that social participation is the «nuclear» basis of «empowerment». In the experience of social participation, the capabilities of an older person are expanded, the strength and significance of age communities are strengthened; constructive social spaces and relationships are created by their hands. Participatory practices become broadcasters of the culture of participation, allow you to notice the contribution of the older generation, increase the value of age and «deploy» society towards older people and their potential.